2018
DOI: 10.1089/lap.2017.0131
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Rib Resection in Children

Abstract: Benign rib lesions in children are rare. Thoracoscopy may be offered to reduce the functional deleterious consequences of an open surgery. It may be put forward especially in case of hereditary multiple exostoses where redo procedures may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Of these, nine underwent surgery. Furthermore, the review of literature revealed that costal exostoses were actively resected in cases of thoracic complications caused by exostoses, even if prior to adolescence[ 4 , 15 ]. Thoracic complications caused by costal exostoses are serious.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, nine underwent surgery. Furthermore, the review of literature revealed that costal exostoses were actively resected in cases of thoracic complications caused by exostoses, even if prior to adolescence[ 4 , 15 ]. Thoracic complications caused by costal exostoses are serious.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to major thoracotomy, VATS has become an increasingly popular method for treating the intrathoracic lesions because it is a minimally invasive procedure[ 3 ]. VATS appears to be the best option for surgical resection of exostoses to prevent thoracic complications in cases of apparently benign exostoses[ 15 , 16 ]. In addition, VATS may be easily offered in cases of HME because redo VATS is less invasive[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations